2016
DOI: 10.3389/fphar.2016.00230
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Improves Physico-Mechanical Properties and Enhances Endothelialization of Poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/Poly(ε-caprolactone) Small-Diameter Vascular Grafts In vivo

Abstract: The combination of a natural polymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and a synthetic hydrophobic polymer poly(ε-caprolactone) (PCL) is promising for the preparation of biodegradable and biocompatible small-diameter vascular grafts for bypass surgery. However, physico-mechanical properties and endothelialization rate of PHBV/PCL grafts are poor. We suggested that incorporation of vascular endothelial growth factor (VEGF) into PHBV/PCL grafts may improve their physico-mechanical properties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 18 publications
1
35
1
2
Order By: Relevance
“…We previously found that either conjugation with RGD peptides or incorporation of VEGF improve biophysical properties of electrospun PHBV/PCL small-diameter vascular grafts [22,23]. Modification with VEGF reduced mean pore area and mean fiber diameter in comparison with modification with RGD peptides [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously found that either conjugation with RGD peptides or incorporation of VEGF improve biophysical properties of electrospun PHBV/PCL small-diameter vascular grafts [22,23]. Modification with VEGF reduced mean pore area and mean fiber diameter in comparison with modification with RGD peptides [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Modification with VEGF reduced mean pore area and mean fiber diameter in comparison with modification with RGD peptides [22,23]. Grafts with incorporated VEGF consisted mostly of nanofibers; on the contrary, those with RGD were formed mostly of microfibers [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations